IMPULSIVE BUYING DITINJAU DARI KONTROL DIRI PADA MAHASISWI PENGGEMAR K-POP DI YOGYAKARTA - Dewi Puspitasari; Siti Hafsah Budi Argiati; Flora Grace Putrianti (Journal of Psychology Students, 2022)
AbstractThis study aims to determine the relationship between self-control and impulsive buying of female K-Pop fans. The subjects of this study were female K-Pop fans who joined the "X" fan club in Yogyakarta, which were taken using a purposive sampling technique. The measuring instrument in this study is the self-control scale and the impulsive buying scale. The self-control scale is based on the Averil aspect and the impulsive buying scale is based on the Rook aspect. This research uses descriptive quantitative. The data analysis method used is the product-moment correlation with the help of the SPSS statistics 16.0 program computer program for windows. The results of this study indicate that there is a negative relationship between self-control and impulsive buying of (r) = 0.888 p = 0.000 which means the higher the self-control, the lower the impulsive buying behavior, and the lower the self-control, the higher the impulsive buying behavior. These results indicate that the hypothesis is accepted, meaning that there is a significant negative relationship between self-control and impulsive buying. The contribution of self-control to impulsive buying is 77.44% and the remaining 22.56% is influenced by other factors not measured in this study.